2020
DOI: 10.1126/sciadv.abb6242
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific genetic features inform prediction of drug side effects in clinical trials

Abstract: Adverse side effects often account for the failure of drug clinical trials. We evaluated whether a phenome-wide association study (PheWAS) of 1167 phenotypes in >360,000 U.K. Biobank individuals, in combination with gene expression and expression quantitative trait loci (eQTL) in 48 tissues, can inform prediction of drug side effects in clinical trials. We determined that drug target genes with five genetic features—tissue specificity of gene expression, Mendelian associations, phenotype- and tissue-level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…To further demonstrate functionality of the phenome-wide map, we tested for enrichment of colocalized genes and phenotypes in the phenome-wide map with drug side effects in corresponding drug target genes in an adapted integrated clinical trial dataset of 1,780 drugs [25] (see Methods ) in each of the 48 GTEx tissues, adjusting for co-cluster grouping. In almost all tissues, we observed marked enrichments of reported drug side effects with colocalized target genes and phenotypes ( Figure 4 ; Table S5, Additional file 1 ), with the strongest associated odds ratio (OR) observed in “Minor Salivary Gland” (OR = 86.43, 95% confidence interval (CI) = (11.596 – 11,078.85), p-value = 6.12 × 10 −11 ), in “Breast - Mammary Tissue” (OR = 10.98, 95% CI = (3.514 – 54.897), p-value = 2.19 × 10 −6 ) and in “Cells - EBV-transformed lymphocytes” (OR = 7.03, 95% CI = (2.070 - 28.367), p-value = 1.43 × 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further demonstrate functionality of the phenome-wide map, we tested for enrichment of colocalized genes and phenotypes in the phenome-wide map with drug side effects in corresponding drug target genes in an adapted integrated clinical trial dataset of 1,780 drugs [25] (see Methods ) in each of the 48 GTEx tissues, adjusting for co-cluster grouping. In almost all tissues, we observed marked enrichments of reported drug side effects with colocalized target genes and phenotypes ( Figure 4 ; Table S5, Additional file 1 ), with the strongest associated odds ratio (OR) observed in “Minor Salivary Gland” (OR = 86.43, 95% confidence interval (CI) = (11.596 – 11,078.85), p-value = 6.12 × 10 −11 ), in “Breast - Mammary Tissue” (OR = 10.98, 95% CI = (3.514 – 54.897), p-value = 2.19 × 10 −6 ) and in “Cells - EBV-transformed lymphocytes” (OR = 7.03, 95% CI = (2.070 - 28.367), p-value = 1.43 × 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To test if the identified co-clusters were enriched with target genes with reported drug side effects for relevant phenotypes, we used our integrated clinical-genetic drug side effect dataset described and published in [25]. This consists of 1,780 drugs and their gene targets with side effect and coloc2 results mapped to 48 GTEx terms (see [25] for mapping approach).…”
Section: Drug Side Effects Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous phenome-wide association study in combination with tissue-specific gene expression and eQTL showed that the presence of eQTL in multiple tissues resulted in more unique phenotypes driven by genome-wide association loci and drugs delivered to multiple tissues can induce several side effects (Duffy et al, 2020). More importantly, recent establishment of an amount of publicly available databases based large-scale omics provided a timely opportunity to understand the effects and safety of target drugs across populations.…”
Section: Discussionmentioning
confidence: 99%